Carbapenem treatment options for metallo-beta-lactamase: drug screening and dose optimization of meropenem-based combinations against NDM- or IMP-producing Klebsiella pneumoniae - Che, Haoyue; Hu, Bo; Cui, Xiaoming; Yang, Jiyong; Zeng, Jinru; Dong, Liuhan; Wang, Rui; Cai, Yun (Frontiers in Microbiology, 2025)
BackgroundThe global dissemination of carbapenemase-producing Klebsiella pneumoniae (CPKP) has been occurring at an alarming pace, especially for the metallo-β-lactamase (MBL) group. Current clinical data suggest that carbapenem is still irreplaceable in terms of safety and efficacy. For MBL-producing Klebsiella pneumoniae (MBL-KP), how to use carbapenem judiciously in the context of advocating carbapenem-sparing strategies remains largely undetermined.MethodsFour strains carrying different MBLs (two IMPs and two NDMs) were collected. The genome sequence, drug resistance phenotype, and synergistic effect of different meropenem-based antimicrobial combinations were tested. Dynamics in vitro pharmacokinetic/pharmacodynamic (PK/PD) model was used to optimize the dosage. The selected combination regimens were verified in a murine model of peritoneal sepsis.ResultsMeropenem in combination with fosfomycin or colistin was effective against MBL-KP strains. Meropenem in combination with colistin had a better bactericidal effect compared with fosfomycin, while such a combination was prone to cause colistin-dependent heterogeneous resistance, especially for IMP-KP. For NDM-KP extremely resistant to meropenem, ultra-high dose up to 2.75 g q6h meropenem in combination with fosfomycin or colistin was needed. For IMP-KP, high-dose meropenem monotherapy (2 g q8h) or low-dose meropenem (1 g q8h) in combination with fosfomycin were both feasible.ConclusionMeropenem in combination with fosfomycin or colistin was an effective choice for MBL-KP. The combination regimen and dosage optimization should be assessed based on not only the type of enzyme but also the specific value of minimum inhibitory concentration (MIC).